PENGARUH GREEN BRAND IMAGE DAN GREEN PERCEIVED VALUE TERHADAP GREEN TRUST DAN GREEN BRAND EQUITY - Christiana Naftalia, A. A. Sagung Mas; Suparna, Gede (E-Jurnal Manajemen, 2017)
ABSTRACT People globally are becoming aware of the environmental changes caused by global warming. With the phenomenon of the environment, interesting to be studied as well as a research objective is to explain the effect of green brand image and green perceived value on green trust and green brand equity on the product of Jamu Sido Appears In Denpasar City with green trust as a mediation variable. This study was conducted in Denpasar City with the number of samples as much as 112 respondents users of herbal products Sido Muncul. The sample was determined using non-probability sampling model, with purposive sampling technique. The data that have been collected is processed using path analysis technique. Partially, the results show that the green brand image has no significant and positive effect on green trust and green brand equity, green perceived value has significant and positive effect on green trust and green brand equity, then green trust has no significant and positive effect on the green brand Equity.